2006
DOI: 10.1590/s0034-70942006000500006
|View full text |Cite
|
Sign up to set email alerts
|

Efeitos hemodinâmicos e metabólicos imediatos determinados pelas soluções de cloreto de sódio a 7,5% e de sua associação ao dextran 70 a 6% na reanimação do choque hemorrágico: estudo experimental em cães

Abstract: RESUMO

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
1
0
2

Year Published

2007
2007
2010
2010

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 42 publications
(59 reference statements)
1
1
0
2
Order By: Relevance
“…On the other hand, during the reperfusion process occur the reverse mechanism with inversion of flows, and the use of a fluid containing sodium and potassium ions contributes to this increase. In the literature, this sequence was observed, supporting the decrease followed by the increase after the establishment of the reperfusion 18 . During the period of hemorrhagic shock, potassium tends to leave the cell, elevating its serum concentration, but it tends to decrease in reperfusion because of the inverse mechanism.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…On the other hand, during the reperfusion process occur the reverse mechanism with inversion of flows, and the use of a fluid containing sodium and potassium ions contributes to this increase. In the literature, this sequence was observed, supporting the decrease followed by the increase after the establishment of the reperfusion 18 . During the period of hemorrhagic shock, potassium tends to leave the cell, elevating its serum concentration, but it tends to decrease in reperfusion because of the inverse mechanism.…”
Section: Discussionsupporting
confidence: 67%
“…This event was very evident in the results of the study, showing the reduction of PCO 2 just like it was expected. In the literature, it was found a study that observed the elevation of PCO 2 during the progression of the experiment, however it was used, for volemic reposition, NaCl 7,5% associated to dextran 6%, a different solution from the one used in this study 18 . In addition, the elevation of PaO 2 is a sign of compensation due to inappropriate perfusion.…”
Section: Discussionmentioning
confidence: 99%
“…Nos momentos iniciais do tratamento, a diminuição do pH, ocorrida em ambos os grupos, possivelmente foi decorrente da diminuição da perfusão tecidual, gerando um aumento dos níveis de H + e consequentemente a acidose metabólica. Alguns estudos citam a hipercloremia resultante da administração da solução hipertônica de NaCl 7,5% como possível causador de acidose (MELETTI et al, 2006); entretanto, a não mensuração do íon cloro não permite confirmar essa possibilidade no presente estudo. A partir de T15, os valores começaram a aumentar, possivelmente pela utilização das reservas de bicarbonato, com consequente diminuição deste (Tabela 1) na tentativa de compensação da acidose metabólica.…”
Section: Variável Grupounclassified
“…Esse efeito foi observado em todos os momentos em relação ao basal em ambos os grupos (LEE & DROBATZ, 2003). No entanto, os valores de pH continuaram menores que os dados basais em ambos os grupos até o final do período de avaliação, corroborando MELETTI et al (2006).…”
Section: Variável Grupounclassified